Pengembangan Bahan Ajar Fisika Berbasis I-SETS (Islamic, Science, Environment, Technology, Society) Terkomplementasi Kearifan Lokal dan Muatan Karakter (UPEJ Unnes Physics Education Journal, 2020)
This research aims to know the characteristics of instructional materials physics based I-SETS (Islamic, Science, Environment, Technology, Society) complimented of local wisdom and character values and development of students character after using of instructional materials physics. The research methods used are Research and Development with 4D models according to Thiagarajan. The results of this research showed that instructional materials physics have a characteristic of local wisdom and character values, based I-SETS, good of used with a feasibility percentage of 92.74% and are easily understood with a percentage rate of 95% and are practically used with a practicality value of 82%. The development of religious character, curiosity, environmental care and social care students showed an medium increased. It can be concluded that instructional materials physics based I-SETS (Islamic, Science, Environment, Technology, Society) complimented of local wisdom and character values the are very feasible, easy to understand and practical to use in the learning process and can develop the character in the students.